2020
DOI: 10.31234/osf.io/rzvby
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conceptual disorganization and redistribution of resting state cortical hubs in untreated first episode psychosis: A 7T MRI study

Abstract: Background:Network level dysconnectivity has been studied in positive and negative symptoms of schizophrenia. Conceptual disorganization (CD) is a symptom subtype which predicts impaired real-world functioning in psychosis. Systematic reviews have reported aberrant connectivity in formal thought disorder, a construct related to CD. However, no studies have investigated whole-brain functional correlates of CD in psychosis. We sought to investigate brain regions explaining the severity of CD in patients with fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Our findings indicated that the ReHo values of the left PrCG, PoCG, and PCL in first-episode MDD patients significantly decreased after taVNS treatments. The PrCG, PoCG, and PCL belong to the sensorimotor cortex and are engaged in cognitive functions (Wang et al, 2015), disorganized behavior (Dey et al, 2021), emotional processing (Li et al, 2016), and no-planning impulsivity (Zhang R. et al, 2020). Some recent studies have shown that the ReHo and ALFF values of PrCG and PoCG were higher than those of HCs in MDD patients (Xia et al, 2019;Liu et al, 2021;Yan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicated that the ReHo values of the left PrCG, PoCG, and PCL in first-episode MDD patients significantly decreased after taVNS treatments. The PrCG, PoCG, and PCL belong to the sensorimotor cortex and are engaged in cognitive functions (Wang et al, 2015), disorganized behavior (Dey et al, 2021), emotional processing (Li et al, 2016), and no-planning impulsivity (Zhang R. et al, 2020). Some recent studies have shown that the ReHo and ALFF values of PrCG and PoCG were higher than those of HCs in MDD patients (Xia et al, 2019;Liu et al, 2021;Yan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%